Solitomab, an EpCAM/CD3 bispecific antibody construct (BiTE®), is highly active against primary uterine and ovarian carcinosarcoma cell lines in vitro. Issue 1 (December 2015) - Ferrari, Francesca; Bellone, Stefania; Black, Jonathan; Schwab, Carlton; Lopez, Salvatore; Cocco, Emiliano; Bonazzoli, Elena; Predolini, Federica; Menderes, Gulden; Litkouhi, Babak; Ratner, Elena; Silasi, Dan-Arin; et al.
Abstract Background Uterine and ovarian carcinosarcomas (CS) are rare but highly aggressive gynecologic tumors which carry an extremely poor prognosis. We evaluated the expression levels of EpCAM and thein vitro activity of solitomab, a bispecific single-chain antibody construct which targets epithelial-cell-adhesion-molecule (EpCAM) on tumor cells and also contains a CD3 binding region, against primary uterine and ovarian CS cell lines. Methods EpCAM expression was evaluated by flow cytometry in a total of 5 primary CS cell lines. Sensitivity to solitomab-dependent-cellular-cytotoxicity (ADCC) was tested against the panel of primary CS cell lines expressing different levels of EpCAM in standard 4 h51 Cr release-assays. The proliferative activity, activation, cytokine secretion (i.e., Type I vs Type II) and cytotoxicity of solitomab in autologous tumor-associated-T cells (TAL) in the pleural fluid of a CS patient were also evaluated by CFSE and flow-cytometry assays. Results Surface expression of EpCAM was found in 80.0 % (4 out of 5) of the CS cell lines tested by flow cytometry. EpCAM positive cell lines were found resistant to NK or T-cell-mediated killing after exposure to peripheral blood lymphocytes (PBL) in 4-h chromium-release assays (mean killing ± SEM = 1.1 ± 1.6 %, range 0–5.3 % after incubation of EpCAM positive cell lines with control BiTE®). In contrast, after incubation with solitomab, EpCAM positive CS cells became highly sensitive to T-cell-cytotoxicity (mean killing ± SEM of 19.7 ± 6.3 %; range 10.0-32.0 %;P < 0.0001). Ex vivo incubation of autologous TAL with EpCAM expressing malignant cells in pleural effusion with solitomab, resulted in a significant increase in T-cell proliferation in both CD4+ and CD8+ T cells, increase in T-cell activation markers (i.e., CD25 and HLA-DR), and a reduction in number of viable CS cells in the exudate (P < 0.001). Conclusions Solitomab may represent an effective treatment for patients with recurrent/metastatic and/or chemo-resistant CS overexpressing EpCAM.